Assessment of Quality of Life and Urinary and Sexual Function After Radical Hysterectomy in Long-Term Cervical Cancer Survivors. Issue 4 (1st May 2018) - Plotti, Francesco; Terranova, Corrado; Capriglione, Stella; Crispino, Stefania; Li Pomi, Alessandra; de Cicco Nardone, Carlo; Montera, Roberto; Panici, Pierluigi Benedetti; Angioli, Roberto; Scaletta, Giuseppe
Abstract : Aims: The aim of this study was to evaluate long-term quality of life and urinary and sexual function in long-term cervical cancer survivors previously treated with radical hysterectomy (RH) type C2/type III. Methods: All patients who presented at Campus Bio-Medico of Rome for RH type C2/type III for cervical cancer were considered eligible for this retrospective study protocol. We included exclusively patients with complete response to primary treatment with at least 36 months of follow up. Included subjects were interviewed with the European Organization for Research and Treatment of Cancer QLQ-CX24 Questionnaire, European Organization for Research and Treatment of Cancer QLQ-C30, and an Incontinence Impact Questionnaire 7. Results: From January 2004 to June 2014, 251 patients affected by locally advanced cervical cancer were treated at Campus Bio-Medico of Rome treated with type C2/type III RH. At time point of March 2017, 90 patients were included with a mean age of 55.6 ± 8.5 years. The questionnaires were administered after a median follow-up of 49 months after the end of therapy. The symptoms of fatigue, nausea and vomiting, appetite loss, pain, insomnia, and dyspnea, as well as a negative financial impact, were reported as not frequent and rarely disabling. On the contrary, patients frequently reported gastrointestinal complaints. Diarrhea was present in 6% of patients and was referred as mild; constipation was present in 75% of women and was reported as mild in 30% of cases, moderate in 30%, and severe in 15%. Concerning sexual activity, data indicated a good level of sexual enjoyment with a slight worsening of sexual activity. Incontinence was reported in 28% of cases and appeared to be mild and rarely disabling (all mean values <2). Conclusions: Waiting for ongoing randomized controlled trials, this study confirmed that RH may be considered as a useful treatment plan, according to its negligible long-term impact on quality of life, urinary dysfunction, and sexual function.